Work of Professor Zdenko Brusić (Archaeologia Adriatica, 2017)
The paper focuses on life and work of Zdenko Brusić, respected Croatian archaeologist. Zdenko Brusić was born in Šibenik in 1938. He was curator in archaeological collection in Nin and in the Šibenik City Museum. Later, he became a curator in Archaeological museum Zadar. In 1998 he was appointed professor of prehistoric archaeology on the Department of Archaeology of the Faculty of Philosophy in Zadar (now University of Zadar) and rose to full professor by the time he retired in 2008. His contribution to Croatian archaeology is enormous but he will especially be remembered as one of the founders of underwater archaeology in Croatia.
Keywords: Zdenko Brusić; University of Zadar; Archaeological Museum Zadar; archaeology; underwater archaeology